THE INFLUENCE OF ORGANIZATIONAL CULTURE ON INTERNATIONALIZATION OF MAHIDOL UNIVERSITY - Xuan, Qianying (PEOPLE: International Journal of Social Sciences, 2015)
In a knowledge-based global economy, higher education institutions (HEIs) are undergoing great changes in various aspects.The internationalization of HEIs is a natural and inevitable consequence of the globalized economy.With the increasing importance of internationalization in HEIs, the school administrators and stakeholders spare more emphasis on the internationalizing process in their own institutes. Organizational aspects have been assessed by many researchers as a means to understand how it foster or inhibit the process of internationalization of HEIs. Influence of organizational culture on internationalization, has been widely studied in western and European context, but not in Southeast Asia. Thus, this study seeks to assess how organizational culture influences the internationalization of a Thai HEI as a pilot research. The aim of this study is to equip Mahidol University administrators with the ideas that internationalization can be optimized by developing the organizational culture towards the entrepreneurial direction. Understanding the influence of organizational culture on internationalization will increase the leadership effectiveness of Mahidol University management team. It also provides a means for other HEIs in Southeast Asian to assess institutional culture readiness for internationalization.